The Relationship Between Religiousness and Anxiety Levels in Muslim Students Writing Their Theses (Journal of Health, Medical, and Psychological Studies, 2026)
Background: Final-year students generally face academic pressure that can trigger anxiety during the thesis writing process. Religiosity serves as a coping mechanism that is believed to reduce anxiety levels. This study was conducted to examine the relationship between religiosity levels and anxiety levels among students. Objective: To determine the relationship between religiosity levels and anxiety levels among students during the thesis writing process. Methods: This study employed a quantitative design with a cross-sectional approach. The study population consisted of 150 students, using a total sampling technique in which the entire population was included as the sample. Data were collected using a demographic questionnaire, the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS), and the Zung Self-Rating Anxiety Scale (Z-SRAS). Data analysis was performed using Somers’ d correlation test. Results: The majority of respondents experienced moderate levels of anxiety. Bivariate analysis showed a significant relationship between religiosity levels and anxiety levels among students (p-value = 0.001), indicating that higher religiosity levels were associated with lower anxiety levels. Conclusion: There is a significant relationship between religiosity levels and anxiety levels among students during the thesis writing process. Religiosity plays an effective role as a coping mechanism in helping students manage psychological pressure related to academic demands.